SUPLEMENTASI PROTEIN IKAN GABUS SEBAGAI ALTERNATIF DALAM PENATALAKSANAAN DIET PADA PASIEN DENGAN INDIKASI HIPOALBUMINEMIA DI RSUP Prof. Dr. R.D. KANDOU MANADO - Vera T. Harikedua; Rivolta G.M. Walalangi; Olfie Sahelangi (POLTEKKES KEMENKES MANADO, 2014)
Malnutrition in developing countries ( 47-50 % ) is higher as compared to developedcountries is 20-46 % . Some research results reinforce that opinion , where theprevalence of malnutrition in patients new entry in Latin America shows 50.2 points and3 major hospitals in Indonesia ( Sardjito hospital Yogyakarta , Sanglah hospital Bali,Jamil hospital Padang) reported 56.9 % .The results showed a significant increase in albumin levels in patients who receivedpostoperative dietary extra filtrate cork fish . Increase in serum albumin was also noadverse effect to the increase in blood triglycerides . As research results Suprayitno et al. (2003 ) , showed that administration of filtrate cork fish can increase levels of serumalbumin and a new wound healing scar . A set of case studies , providing extrainformation that the administration menu filtrate cork fish was positively correlated withincreased levels of albumin and wound healing process . Increased levels of albumin ,patients who have an extra menu filtrate cork fish are relatively higher than white eggs.The problems of the study is how the effectiveness of catfish protein in patients withhypoalbuminemia indication . Benefits of this research include: to provide a newalternative in the management of diet especially in patients with hypoalbuminemiaindication .This research uses a quasi-experimental design of pre and post test , this study willprovide an overview of the effectiveness of cork fish protein in patients withhypoalbuminemia indication . The experiment was conducted in the department of Prof. .Dr. . R.D. Kandou Manado in July - September 2013 . The population in this study wereall patients with hypoalbuminemia indications shown by the results of laboratory tests .Of the subjects in this study 16 patients with criteria for men and women , cooperative ,and approved informed consent and the approval of the hospital and ethics committeethe Ministry of Health polytechnic Manado . Subjects using the technique of determiningsubjective instrument global assessment ( SGA ).Processing and data analysis using univariate analysis to determine thecharacteristics of the frequency distribution of the variable . Bivariate test by using apaired t - test . Then followed by a multivariate analysis using linear regression .Theresults are significant differences in albumin before and albumin after intervention with -average increase of 0.31 mg / dl . Multivariate test variables explained that the effect ofthe intake of energy , protein , fat and duration of cork fish nuggets on levels of albuminby 60 % , the rest is influenced by other variables not amined .Conclusion there are differences in initial levels of albumin and albumin levels after theend of the intervention, and no catfish nugget effect of the increase in albumin levels ofpatients with hypoalbuminemia